Population dynamics of Indian sarus crane, Grus antigone antigone (Linnaeus, 1758) in and around alwara lake of Kaushambi district (Uttar Pradesh), India - Verma, Ashok Kumar; Prakash, Shri (International Journal of Biological Research, 2016)
Sarus crane is the only resident breeding crane in India. They prefer open habitat like marsh areas, irrigated paddy fields, grass land and river banks. These areas suit them for foraging, roosting and nesting. These cranes are omnivorous birds, feeding aquatic plants, seeds, roots, tubers, crustaceans, insects, molluscs, fishes, frogs, reptiles and avian eggs. These are not only involved in maintaining the food chain and food web but also providing strength to wetland ecosystem. Ecological and environmental condition of this lake is nicely supporting the survival of vulnerable Indian sarus crane, Grus antigone antigone. In general, the population of sarus crane is decreasing at global level but the authors recorded its increasing trends during their exploration from 2011 to 2014 in and around the Alwara lake of Kaushambi district of Uttar Pradesh (India).